Seismic performance of concrete-filled double-skin steel tubes after exposure to fire: Analysis. (November 2019) - Li, Wei; Chen, Bing; Wang, Tao
Abstract: This paper presents numerical analysis on the seismic performance of concrete-filled double-skin steel tubes (CFDST) after exposure to fire. The finite element model with multiple steps is established with considerations of degradations of material properties due to elevated temperatures and post-fire cyclic loading. The numerical model is verified by test results reported in the companion paper and data available from literature. The numerical model is then used to explore the post-fire seismic performance of CFDST columns, where the temperature field, the internal force and stress distribution are analysed. Parametric studies are also carried out, to discuss the influence of the loading path, the duration of heating, the axial load level, the nominal steel ratio, the hollow ratio of the cross section, etc. It is found that the proposed numerical model is capable to simulate the structural behaviour under difference phases, and the loading path could affect the post-fire seismic performance of CFDST columns. Highlights: We establish a finite element model to predict the cyclic behaviour of CFDST column after exposure to fire; We study the load transfer mechanism of CFDST column under cyclic loading after exposure to fire; We discuss the influence of key parameters on the post-fire seismic performance of CFDST column.